MODEL DISEMINASI INFORMASI GEOSPASIAL PULAU-PULAU KECIL TERLUAR BERBASIS PEMANFAATAN PENGINDERAAN JAUH DAN GOOGLE MAPPING SYSTEM - Sarno, Sarno (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2013)
This paper describes the implementation of Geospatial Information and Communication Technology (ICT-Geospatial) in the dissemination of geospatial information of outermost small islands in Indonesia. Dissemination models allow the user via the Internet and web media to easily interact and acquire geospatial information of outermost small islands that are needed through a web browser online. This study is a follow-up development of remote sensing applications of geospatial information "Outermost small islands in Indonesia Based on Three-Dimensional Maps Satellite Imagery and Land Cover Map". Geospatial information has been compiled and published using paper media in the form of albums. ICT-Geospatial has been growing very rapidly, especially the Internet, web media and geospatial information systems. Efforts to develop applications, allowing running processes of dissemination of geospatial information of outermost small islands in Indonesia to the general public through a network of electronic information. Those efforts are carried out through the construction of "Model of Dissemination of Geospatial Information of outermost small Islands Based on Remote Sensing Applications and Google Mapping System". With the establishment of model of dissemination of geospatial information of outermost small islands, it is expected to be a supporting complement of efforts to the dissemination of the information to the broader public and to benefit us all knowing the existence of small islands in the outer region of the Republic of Indonesia, so the society can participate in maintaining security, establishing and enforcing the boundaries; managing the natural resource/agriculture sustainably, taking part in the safety and preservation of natural resources.